1970
DOI: 10.1139/v70-518
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) and nickel(II) complexes of some bidentate imidazoline ligands. Stereochemically dependent derealization in the imidazoline rings

Abstract: Tetrahedral and octahedral cobalt(II), and square and octahedral nickel(I1) complexes of 1,2-bis(2'-imidazolin-2'-yl)benzene, 1,2-bis(2'-imidazolin-2'-yl)ethane, and some imidazoline ring methyl substituted ligands are reported. The structures are confirmed by three X-ray structural analyses, magnetism, and electronic and vibrational (conventional and far i.r.) spectroscopy. Both cis and trans octahedral complexes of the type M(ligand)z(NCS)z [M = Co(II), Ni(II)] have been characterized, and none of these exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The lower energy absorptions in these regions associated with IV confirm the presence of coordinated bromine and suggest a structure similar to that in 111. These spectral bands are typical of pseudo-tetrahedral cobalt(I1) complexes with CoN2X2 chromophores and the absorption energies compare closely with bands observed for analogous, mononuclear complexes involving the ligands 1,2-bis(4,5-dihydroimidazol-2-yl)benzene(LP) and 1,2-bis(benzothiazo1-2-yl)ethane(BBTE), which have very similar donor groups producing equivalent, seven membered chelate rings (8,9). In DMF solution I11 and IV exhibit v3 and v, transitions with almost identical absorption energies.…”
Section: Spectroscopy and Magnetismsupporting
confidence: 57%
“…The lower energy absorptions in these regions associated with IV confirm the presence of coordinated bromine and suggest a structure similar to that in 111. These spectral bands are typical of pseudo-tetrahedral cobalt(I1) complexes with CoN2X2 chromophores and the absorption energies compare closely with bands observed for analogous, mononuclear complexes involving the ligands 1,2-bis(4,5-dihydroimidazol-2-yl)benzene(LP) and 1,2-bis(benzothiazo1-2-yl)ethane(BBTE), which have very similar donor groups producing equivalent, seven membered chelate rings (8,9). In DMF solution I11 and IV exhibit v3 and v, transitions with almost identical absorption energies.…”
Section: Spectroscopy and Magnetismsupporting
confidence: 57%
“…A review of the literature revealed that 1,2-bis(2-benzothiazolyl)benzene and 1,2-bis(2-benzothiazolyl)ethane are frequently used as ligands and a considerable number of their complexes with late transition metals are reported [1][2][3][4][5][6] . Also, the nickel(II), cobalt(II) and copper(II) coordination chemistry of some tetradentate ligands involving benzothiazole functional groups has been published 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The ligand 2, 6-bis (2-benzothiazolyl) pyridine9, 10, has been shown to behave as an N-3 donor in its complexes with manganese (II), iron (II) and nickel (II). 2,6-Bis(benzimidazolyl)pyridine 1,[11][12][13][14][15][16][17][18][19][20][21][22][23] , and 2,6-bis (benzoxazolyl)pyridine 24 , derivatives have been reported as ligands for transition metals in order to investigate the complexes for their structures and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiazole contains a heterocyclic sulfur atom and a pseudo-imidazole functional group. A review of the literature revealed that 1,2-bis(2-benzothiazolyl)benzene and 1,2-bis(2-benzo-thiazolyl)ethane are frequently used as ligands and a considerable number of complexes with late transition metals are reported [7][8][9][10][11][12]. Also, the nickel(II), cobalt(II) and copper(II) coordination chemistry of some tetradentate ligands involving benzothiazole functional groups has been published [13].…”
Section: Introductionmentioning
confidence: 99%